Effects of vitamin D supplementation in patients with rheumatoid arthritis: A systematic review and meta-analysis - Mahsa Ranjbar; Mehran Rahimlou; Maryam Fallah; Kurosh Djafarian; Hamed Mohammadi (Heliyon)
Background: Rheumatoid arthritis (RA) is known as an inflammatory illness. Evidence shows that Vitamin D modulates immunologic function and inflammation by affecting various immunological cells. We decided to run a systematic review and meta-analysis to investigate the relationship between vitamin D supplementation and the outcomes of adult patients suffering from RA. Methods: We searched electronic databases, using specific search terms in PubMed, Scopus, and ISI Web of Science, until May 2024. Clinical studies involving patients with RA were included if they compared the effects of vitamin D supplementation to either a placebo or standard care. The results from the selected studies were presented as weighted mean differences (WMD) along with a 95 % confidence interval (CI). Results: Inclusion criteria have been met by 11 studies and presented as part of this analysis. The results indicate a major influence of vitamin D supplementation on the Disease Activity Score 28 (DAS-28) (WMD: −0.83, 95 % CI: −1.38 to −0.28, p-value <0.001), C-reactive protein (CRP) level (WMD: −0.24, 95 % CI: −0.45 to −0.03, p-value = 0.03), erythrocyte sedimentation rate (ESR) level (WMD: −4.08, 95 % CI: −4.67 to −3.50, p-value <0.001), serum vitamin D level (WMD: 12.69, 95 % CI: 1.80 to 23.59, p-value = 0.02), and non-significant effect on the health assessment questionnaire (HAQ) and visual analog scale on pain (VAS-pain) scores. Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) assessment shows moderate certainty of the evidence for all outcomes except for serum vitamin D, which has a high certainty of the evidence. Conclusion: To improve DAS-28, CRP, ESR, and serum vitamin D in RA patients, vitamin D supplements may be beneficial, although the optimal dosage and length of treatment are still unknown.